DOSIMETRIC EVALUATION AND MATHEMATICAL MODELING OF AIR KERMA IN LOWER EXTREMITY RADIOGRAPHY - Maslebu, Giner; Muninggar, Jodelin; Tita, Faldy; Yulandewi, Yemima Sandra; Prakoso, Harya Abdi; Koleba, Mauren Abigail (Jurnal Ilmiah Ilmu Terapan Universitas Jambi, 2026)
Achieving an optimal balance between diagnostic image quality and radiation dosimetry is foundational to effective diagnostic imaging and the ALARA principle. The aim of this study is to analyze Incident Air Kerma (INAK) and Entrance Surface Air Kerma (ESAK) values from general radiograph examination to evaluate diagnostic efficacy and radiation safety. Baseline data were collected from quality control compliance testing of a Radnext32 Hitachi Computed Radiography system. Subsequently, data analysis was conducted on a lower extremity radiographic survey, encompassing over 30 patients per region using a constant focus-to-film distance of 100 cm.  By using graph plotting tool in Microsoft excel, it revealed a robust correlation between tube voltage (kV) and INAK (R2>0.99), modeled by the power function trendline y=5.10-6x2,1593. Femur examinations result in the highest ESAK values (0.20–0.60 mGy, outliers to 0.92 mGy), while genu, cruris, and ankle doses clustered tightly between 0.04–0.37 mGy. All values complied with the Indonesia Dose Reference Level (I-DRL) and IAEA guidelines. Radiation dose correlated linearly with body weight, though data dispersion suggests confounding anthropometric variables (sex, age, height) influence optimization. Discussion: This study establishes critical baseline dosimetry for lower extremity radiography. Its novelty lies in establishing a precise mathematical power function to predict INAK and ESAK changes specifically for lower extremities based on real-world clinical data. These findings advance radiation research by highlighting that standard weight-based dosing is insufficient; future optimization protocols must multi-variably integrate diverse patient anthropometrics and mandatory source-to-surface distance measurement to refine clinical standard operating procedures.